Look-ahead Cruise Control Considering Traffic Information Based on Floating Car Data - Mihály, A.; Gáspár, P. (Acta Technica Jaurinensis, 2013)
The paper focuses on the design of an adaptive cruise control system which optimizes the longitudinal energy and fuel consumption of the vehicle. In the velocity design process a look-ahead method is used considering road information of road sections ahead of the vehicle. By using road information about the characteristics of the oncoming road sections, e.g. oncoming speed limits or road slopes, it is possible to modify the speed during the journey in advance. The main novelty of the paper is the adaptation of forward traffic mean speed in the look-ahead control algorithm. It is demonstrated in real data simulation that with the proposed method significant amount of fuel can be saved compared to a conventional cruise control or a human driver.